Future psychiatric services in Italy: lesson from the COVID-19 pandemic - Pelizza, Lorenzo; Pupo, Simona (Acta Biomedica Atenei Parmensis, 2020)
During the COVID-19 epidemic, home care and remote working showed important technological innovations, leading to review all public mental health policies. In this article, some considerations based on the Italian COVID-19 experience in order to plan post-COVID psychiatric interventions are reported.